Environmental footprint design tool: Exchanging geographical information system and computer-aided design data in real time. (December 2016) - Mark, Earl; Ultmann, Zita
The pairing of computer-aided design and geographical information system data creates an opportunity to connect an architectural design process with a robust analysis of its environmental constraints. Yet, the geographical information system data may be too overwhelmingly complex to be fully used in computer-aided design without computer-assisted methods of filtering relevant information. This article reports on the implementation of an integrated environment for three-dimensional computer-aided design and environmental impact. The project focused on a two-way data exchange between geographical information system and computer-aided design in building design. While the two different technologies may rely on separate representational models, in combination they can provide a more complete view of the natural and built environment. The challenge in integration is that of bridging the differences in analytical methods and database formats. Our approach is rooted in part in constraint-based design methods, well established in computer-aided design (e.g. Sketchpad, Generative Components, and computer-aided three-dimensional interactive application). Within such computer-aided design systems, geometrical transformations may be intentionally constrained to help enforce a set of design determinants. Although this current implementation modestly relates to geometrical constraints, the use of probabilistic risk values is more central to its methodology.